The effect of the presence and severity of bronchiectasis on the respiratory functions, exercise capacity, dyspnea perception, and quality of life in patients with chronic obstructive pulmonary disease - Sahin, Hulya (Ann Thorac Med, 2020)
BACKGROUND: Bronchiectasis is common in patients with advanced chronic obstructive pulmonary disease (COPD) and adversely affects the patients' clinical condition. This study aimed to investigate the effects of bronchiectasis on exercise capacity, dyspnea perception, disease-specific quality of life, and psychological status in patients with COPD and determine the extent of these adverse effects by the severity of bronchiectasis. METHODS: A total of 387 COPD patients (245 patients with only COPD [Group 1] and 142 COPD patients with accompanying bronchiectasis [Group 2]) were included in the study. The patients in Group 2 were divided into three subgroups as mild, moderate, and severe using the Bronchiectasis Severity Index. Six-minute walk distance, dyspnea perception, St. George's Respiratory Questionnaire (SGRQ), and hospital anxiety and depression scores were compared between the groups. RESULTS: In Group 2, dyspnea perception, SGRQ total scores, depression score were higher, and walking distance was lower (P = 0.001, P = 0.007, P = 0.001, and P = 0.011, respectively). Group 2 had significantly worse arterial blood gas values. Dyspnea perception increased with the increasing severity in Group 2 (P < 0.001). Walking distance was lower in patients with severe bronchiectasis (P < 0.001). SGRQ total score, anxiety, and depression scores were significantly higher in the severe subgroup (P < 0.001, P = 0.003, and P = 0.002, respectively). CONCLUSIONS: In patients with Stage 3 and 4 COPD, the presence of bronchiectasis adversely affects the clinical status of the patients, decreases their exercise capacity, deteriorates their quality of life, and disrupts their psychological status. Investigating the presence of bronchiectasis in COPD patients is crucial for early diagnosis and proper treatment.